The impact of customer assisted knowledge production capacity on customer capital in a knowledge-based center - Mohammad Reza Zahedi; Shayan Naghdi Khanachah (Annals of Management and Organization Research)
Purpose: The purpose of this research is to investigate the impact of customer-assisted knowledge production capacity on customer capital. Research methodology: The statistical population of the study consisted of 70 managers, researchers and experts of a scientific center and the statistical sample was counted and estimated 70 persons. The research instrument of the researcher-made questionnaire consists of six dimensions: ability to identify customer needs, create and manage a customer information system, customer loyalty, market share, customer service capability and target customer identification. The validity of the questionnaire was estimated 0.94%. Results: The results show that the impact of customer knowledge production capacity on all dimensions of customer capital is significant. Also, most influential among customer capital factors is customer service capability. Finally, by confirming the research hypotheses, suggestions were made based on the results of the research to improve the client's capital of the statistical society. Limitation: This research only described Knowledge Based Center. Contribution: Organizations realized that relying on existing knowledge alone was not enough to compete in a competitive environment, and went beyond the boundaries of their organization to acquire knowledge. Organizations considered customers as a very useful and knowledgeable resource, and activities should be done to interact with customers in leading organizations. Keywords: Customer assisted knowledge production capacity, Customer capital, Intellectual capital, Knowledge management